Pengabdian Donor Darah pada Masyarakat Sidanegara Cilacap - Issusilaningtyas, Elisa; Pertiwi, Yuniariana; Rochmah, Nikmah Nuur; Aji, Ajeng Puspo; Yulianto, Asep Nurrahman; Yogawati, Nursanti Dwi; Faoziyah, Anita Ratna; Wardani, Tri Kusuma (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
The scarcity of blood is assumed to be caused by a lack of public knowledge about blood donation. Donor health advantages can minimize the danger of cancer, help with weight loss, make the body psychologically better and prolong life, reduce the risk of heart and blood vessel disease, and detect major disorders. Aside from carrying out the Tri Dharma of Higher Education, community service activities seek to encourage local residents to donate blood for the safety of others, hence raising people's desire and willingness to contribute. PMI Cilacap supports this program by sending numerous medical personnel to perform blood draws. The service team distributed information about the benefits of blood donation during this activity. There were 62 registered blood donors, with 43 (69.35%) passing the health check and donating blood, and 19 (30.65%) failing (not passing) the health check and so unable to donate blood.